In Situ Transmission Electron Microscopy for Energy Materials and Devices. Issue 33 (11th June 2019) - Fan, Zheng; Zhang, Liqiang; Baumann, Daniel; Mei, Lin; Yao, Yuxing; Duan, Xidong; Shi, Yumeng; Huang, Jianyu; Huang, Yu; Duan, Xiangfeng
Abstract: Energy devices such as rechargeable batteries, fuel cells, and solar cells are central to powering a renewable, mobile, and electrified future. To advance these devices requires a fundamental understanding of the complex chemical reactions, material transformations, and charge flow that are associated with energy conversion processes. Analytical in situ transmission electron microscopy (TEM) offers a powerful tool for directly visualizing these complex processes at the atomic scale in real time and in operando. Recent advancements in energy materials and devices that have been enabled by in situ TEM are reviewed. First, the evolutionary development of TEM nanocells from the open‐cell configuration to the closed‐cell, and finally the full‐cell, is reviewed. Next, in situ TEM studies of rechargeable ion batteries in a practical operation environment are explored, followed by applications of in situ TEM for direct observation of electrocatalyst formation, evolution, and degradation in proton‐exchange membrane fuel cells, and fundamental investigations of new energy materials such as perovskites for solar cells. Finally, recent advances in the use of environmental TEM and cryogenic electron microscopy in probing clean‐energy materials are presented and emerging opportunities and challenges in in situ TEM research of energy materials and devices are discussed. Abstract : The most recent developments in in situ transmission electron microscopy for studying green‐energy materials and devices such as rechargeable ion batteries, chemical fuel cells, and perovskite solar cells are reviewed. A critical view on the application of this technology on the long road toward a green‐energy future is provided.